Monetary Operations and Central Bank Balance Sheets in a World of Limited Government Securities - Zelmer, Mark (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2001)
The limited supply of government securities in some industrial countries has important ramifications for the operating techniques used by central banks to implement monetary policy, provide credit to the financial sector, and also for the assets they hold on their balance sheets. The paper reviews the salient facts regarding industrial central bank balance sheets and operating techniques, and outlines different options for dealing with a limited supply of government securities. The main conclusion is that central banks may wish to consider extending credit using a broad range of assets as collateral, and engage in outright transactions of securities guaranteed by financial institutions.